EKSISTENSI NILAI-NILAI DAKWAH DI KALANGAN GENERASI Z - Harahap, Siti Rahma (JURNAL MANAJEMEN DAKWAH, 2022)
Today’s technological developments have greatly influenced people’s lives and caused various shifts in attitude, both social, cultural, ethical, and existing norms. Likewise, da’wah activities with the use of the internet and social media have experienced a shift. Previously da’wah was carried out conventionally, but this method is no longer effective, especially for generation Z residents. Generation Z is inseparable from the internet for all types of activities. Therefore, reviewing the existence and values of da’wah with the use of social media in generation Z is the goal of this study. This research is a qualitative descriptive, with the analysis technique of the Miles Huberman model divided into three stages of data processing; data reduction, data presentation, and drawing conclusions or verification. The results of this study indicate that social media has an important role in the continuity of da’wah activities, with its existence among generation Z are the main targets of the preachers. Da’wah through social media has the most prevalence among Generation Z since, in general, they prefer to sit down and listen to traditional da’wah materials. Additionally, the existence of social media as a tool for da’wah comprises many da’wah values, including artistic and equality values, Islam, pluralism, and modernism.